VARIASI KOMPOSISI INPUT PROSES ANAEROBIK UNTUK PRODUKSI BIOGAS PADA PENANGANAN LIMBAH CAIR KOPI - Elida Novita; Sri Wahyuningsih; Hendra Andiananta Pradana (JURNAL AGROTEKNOLOGI, 2018)
Generally, there are two methods of coffee processing beans that are the dry processing and wet processing. The wet coffee processing will produce waste water containing organic materials. The high contain of organic matter in coffee wastewater can be used as biogas through anaerobic process. The biogas production from this processcould have variation of volume and composition depends on their feeding. The purposes of this research were to find the best biogas volume would be produced based on variation of input in batch feeding method (1) and to reduce coffee wastewater concentration by anaerobic process (2). The researched procedures were inoculum production, incubating adaptation and variation of batch feeding into the anaerobic reactor (4 variations). The variation of batch feeding were (1) 1:1; (2) 3:1; (3) 3.7:0.3 for water and (4) 3.6 : 0.4 for cow dung. The highest biogas volume and pollution load reduction were occurred in batch feeding composition 1:1. The volume of biogas production was 250 mL at day 6 and the percentage of parameters reduction were COD 57.35% and BOD 57%. Based on this research, there were also increasing gas volume from day 2 (95 ml) up to day 6 (250 ml) in each batch. Keywords: anaerobic process, biogas, coffee wastewater treatment, input variation